An examination of the charter and proceedings of the Hudson's Bay Company, with reference to the grant of Vancouver's Island [electronic resource] - Fitzgerald, James Edward, 1818-1896; Martin, R. Montgomery (Robert Montgomery), 1803?-1868. The Hudson' s Bay territories and Vancouver's Island. (London : T. Saunders, 1849)
Includes publisher's list. A reply to Robert Montgomery Martin's "The Hudson's Bay territories and Vancouver's Island" (London, 1849). Electronic reproduction. Mode of access: Internet. 44